2010
DOI: 10.1038/eye.2010.168
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of intravenous ketorolac for pain relief in single-stage adjustable strabismus surgery: a prospective, randomized, placebo-controlled trial

Abstract: Purpose To determine the efficacy of preoperative intravenous ketorolac in reducing intraoperative and postoperative pain and improving patient satisfaction in patients undergoing single-stage adjustable strabismus surgery. Methods A prospective, randomized, placebo-controlled clinical trial was performed with 67 patients who underwent horizontal recti muscle surgery with adjustable sutures. The test group received intravenous ketorolac (60 mg) before surgery, and the control group received intravenous normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…This quality improvement initiative reports meaningful reductions in the incidence of moderate to severe postoperative pain following strabismus surgery from 47.3% to 21% as delivered by the implementation of an evidence‐based perioperative care bundle . We present the results of a second analysis from a single QI project that previously reported successful decrease in rates of PONV .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This quality improvement initiative reports meaningful reductions in the incidence of moderate to severe postoperative pain following strabismus surgery from 47.3% to 21% as delivered by the implementation of an evidence‐based perioperative care bundle . We present the results of a second analysis from a single QI project that previously reported successful decrease in rates of PONV .…”
Section: Discussionmentioning
confidence: 89%
“…We devised and introduced our first intervention as an evidence‐based intraoperative bundle (Figure ). This bundle requested five key medications be administered during the pre and intraoperative period: preoperative acetaminophen (or intraoperative acetaminophen via suppository); two anti‐emetics from dexamethasone/ondansetron/dimenhydrinate; ketorolac; and a long‐acting opioid (morphine or hydromorphone) . The perioperative bundle was launched in July 2015 and immediately prior to launch, a “Grand Rounds” presentation was delivered to all members of anesthesiology, ophthalmology, and PACU.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, surgeons make an effort to reduce the surgery-associated pain during and after surgery. 9,11,12 We found that most patients did not experience as much postoperative pain as they were expecting, but that patients who had had surgery involving the vertical or oblique muscles felt significantly more pain than they had expected. Therefore, patients undergoing these types of procedures should be informed of this possibility, and postoperative pain control should be addressed.…”
Section: Discussionmentioning
confidence: 56%
“…9,11,12,16,17 In addition, providing careful and detailed informed consent helps patients undergoing strabismus surgery to relax before surgery. However, we believe that the 8 postoperative symptoms that were investigated in this study cannot be completely alleviated by medications and informed consent.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with previous reports who indicated that pains are difficult to tell from symptoms of EA [ 26 , 27 ]. Strabismus surgery in adults produced minimal postoperative pain which was controlled well with non-opioid drugs like oral acetaminophen, whether it was under general anesthesia or local ocular anesthesia, the reported pain scores in our study should be interpreted cautiously[ 37 ]. No painful examination such as MRI, children experienced EA after inhalation general anesthesia, and fentanyl was effective for EA after MRI [ 5 ].…”
Section: Discussionmentioning
confidence: 99%